A study of the active tectonics and deformation in the Mygdonia basin (N. Greece) using seismological and neotectonic data - PAPAZACHOS, C. B.; VAMVAKARIS, D. A.; VARGEMEZIS, G. N.; AIDONA, E. V. (Bulletin of the Geological Society of Greece, 2001)
In the present work we study the active tectonics setting and related deformation scheme in the Mygdonia basin, on the basis of the joint interpretation of seismological and neotectonic data. For this reason, the stress field derived from fault plane solutions of small-magnitude events from a local seismological experiment, as well as neotectonic observations are studied in order to determine its spatial distribution. The results show an almost identical spatial variation of the stress field determined from the two independent data sets, which also exhibits a very good correlation with the geomorphological changes in the Mygdonia basin. Moreover, the average stress field is almost identical to the corresponding stress pattern determined from the 3 largest events in the study area for which reliable fault plane solutions are available. Using the combined stress pattern and the corresponding moment-rate tensors derived from both data sets, the active crustal deformation is studied for the most active sections of the Mygdonia basin system. The results show a N-S extension at an average rate of 3mm/ yr for the central part of the Mygdonia system, in very good agreement with the available geodetic results.